Teologi Sosial Masyarakat Pinggiran (Konsep Teologi Kaum Perempuan Dalam Memaknai Banjir di Kecamatan Undaan Kabupaten Kudus) - shofaussamawati, shofaussamawati; Listiana, Anisa (PALASTREN: Jurnal Studi Gender, 2018)
The Undaan Kudus Community is the majority of farmers on the outskirts of the industrial city, Kudus, which are often affected by floods. Responding to these conditions the women of Undaan have ways and systems to consolidate existing elements through religious and cultural values. The religious and cultural values they use are in the form of recitation, yasinan, hadrah every Friday night and Monday night. The activities that shape the structure of their view of floods that often hit are different from those in other areas. For them, disaster or flood disaster is a part of life affairs that must be addressed wisely, recovery, rehabilitation and resilience. This study discusses how the theological transformation of Undaan women in interpreting the flood cycle in the Undaan region? The results show that Undaan women's theology views floods as a symbol of collective destruction, destruction of meaning, and dealing with danger. Therefore the ethics of dealing with floods is istirja ', patience, learning, and obedience to God.